The value-driving acquisition process – conceptual framework & business case - Mroczyński, Wojciech G. (Budowanie wartości w procesie akwizycyjnym – koncepcja struktury i przypadek biznesowy, 2022)
The article addresses three challenges in the M&A theory and practice: poor value orientation, lack of integrated approach to an acquisition process, and limited integration scope. It integrates the existing literature reviewing existing models as well as the author’s merger experience. This paper proposes a novel acquisition framework addressing the challenges and gaps in the M&A value-creation process. The framework emphasises the role of corporate strategy as the key value creation formula in setting the right context for a merger. It also reiterates the importance of a performance management system assuring accountability and alignment at every stage of a merger including two new process stages. The model also offers a novel perspective on merger integration challenging the traditional approach and promoting earlier initiation of integration efforts. The paper also demonstrates, through a business case, a practical application of the proposed framework by a serial acquirer.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2022; vol. 66, nr 1, s. 74-100
Keywords: acquisition process; performance management system; value creation; value-driving; proces akwizycyjny; model biznesowy; integracja; system zarządzania wynikami; kreowanie wartości